The Association of Plasma Selenium and Selenoprotein P Levels with Depression Severity and Anxiety Symptoms Among Medical Students in Latvia - Zanda Birģele; Paula Marija Vimba; Anastasija Ševčenko; Andrejs Šķesters; Gunta Ancāne; Laura Valaine (Medicina)
Background and Objectives: Oxidative stress has been identified as a key process involved in different diseases, particularly depression. Selenium (Se) protects against oxidative stress, one of the pathogenic mechanisms involved in affective disorders. Selenium is incorporated into antioxidant selenoproteins, such as selenoprotein P, which acts as the main selenium-transport protein in plasma and as an extracellular oxidant defense mechanism. This study aimed to determine whether lower selenium and selenoprotein P levels correlate with high levels of depression and anxiety symptoms. Materials and Methods: The research design was a quantitative cross-sectional study among employed fourth-year medical students at Riga Stradins University in Latvia. The respondents were selected using convenience samples. The symptoms of anxiety were assessed using the Generalized Anxiety Disorder-7 (GAD-7) scale, and the symptoms of depression were assessed using the Patient Health Questionnaire-9 (PHQ-9) scale. Results: A total of 32 respondents participated; 90.6% (n = 29) were female. A significant association was found between selenoprotein P and symptoms of depression (p = 0.006), as well as between selenoprotein P and symptoms of anxiety (p = 0.012). The median selenium level was not significantly lower (p = 0.214) in the study group compared to the control group. Conclusions: There is a statistically significant correlation between selenoprotein P and symptoms of depression and anxiety, and there is a tendency for students with symptoms of depression and anxiety to have lower selenium levels. However, alternative unrecognized oxidative stress mechanisms involved in the development of symptoms of depression and anxiety, involving selenium and selenoprotein P pathways, may exist. Consequently, further research assessing possible alternative pathways and the effect size is required.